Nxopaxopo wa switandzhaku swa vuguduka eka matsalwa ya xiTsonga lama nga hlawuriwa - Khoza, L. H. (University of Limpopo, 2014)
Problem Statement This proposal investigates the life of men who left their beloved families with the aim of seeking jobs in order to support them. Most of the men when they get employed, they forget about where they come from and start new families by marrying another wives in urban areas. Furthermore this study will seek to find out how these men could get help and to restore their dignity. Methodology In order to achieve the aim and objectives of this proposal, the researcher will utilise textual analysis and interview method. Significance This study will act as wake-up call to the new generation to take into consideration the importance of where they original come from. In addition, the study will contribute to the existing knowledge and understanding the purpose of living their homes to seek employment not to start new families.
h[The investigation of challenges caused by labour migrant system in the selected xiTsonga texts
Thesis (M.A.) --University of Limpopo, 2014
Keywords: Labour migrant system; Migrant labor - South Africa - Limpopo Province